Survey of Gross Motor Skills on Students of State Elementary School 2 Mojoroto, Kediri City - M. Akbar Husein Allsabah; Setyo Harmono (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
Gross motor skills are abilities that must be possessed by any individual that begins to be developed at an early age. The age of 6-12 years is the age when each individual can master gross motor skills so it is necessary to know how the condition of their motor skills can be handled in the future. The purpose of this study was to find out how gross motor skills are in elementary school students. The research design used in this study is descriptive and quantitative with survey methods. The survey conducted by this study used tests and measurements in collecting data. The subjects in this study were 80 elementary school students who were male. The instruments in this study are coordination by throwing catches the ball, agility by using a shuttle run test, speed using a 30-meter sprint test, and balance using the Stork Stand Positional balance test.  The results showed that motor skills in students of Mojoroto state elementary school in Kediri city are included in the good category with a percentage of 59%. Furthermore, in the excellent category, there are 2 students with a percentage of 3%, in the medium category there are 31 students with a percentage of 39%.